Review Procedures Borrowing And Return Record Files Medical Outpatient Medical Record in Health Unit River Candle - Ariska Nurlaila; Devita Farita (Eduvest - Journal of Universal Studies, 2021)
The borrowing of medical record documents at the puskesmas is used for internal or external purposes which include needs in aspects of the usefulness of medical record documents such as administrative, medical, legal, financial, research, and educational aspects. Based on a survey at the puskesmas, the procedure for borrowing and returning medical record files has not been carried out effectively, for example, the return of outpatient medical record files is often not in accordance with the provisions, namely a maximum of 1 (one) hour before the end of working hours, thus hampering the implementation of medical record retrieval at any time. The time is needed by patients, doctors, and parties who need medical record files. The purpose of this study was to determine the procedure for borrowing and returning outpatient medical record files. This research is a type of descriptive research. The object of the research is the procedure for borrowing and returning medical record files of outpatients in the medical record unit. The instruments used are observation guidelines and interview guidelines.